Viewpoint of Working People about Stock Market Investment with Reference to Tiruchirapalli District: An Empirical Study - S. Viji (Current Topics on Business, Economics and Finance Vol. 9, 2023)
In the last several years, there has been a significant shift in the Indian investor community. India currently has a very large investor population and constantly rising investment levels. Along with saving money, risk management, and speculation, some people trade just for fun. "Enjoy investing" and "Enjoy risky propositions" are what they say. In contrast, common trading reasons like saving money and rebalancing only partially account for investor heterogeneity in trading behavior. The simple reason why some people trade significantly more than others and why active traders perform worse than their peers after transaction expenses appears to be entertainment. Individual investment behavior is concerned with decisions regarding the acquisition of modest quantities of securities for one’s own account. Decision tools are frequently used to support investment decisions. It is presumable that the market’s variables and information structure systematically affect both investor choices and market results. This study explored how people in the Tiruchirapalli District behave when it comes to stock trading and how they feel about various types of financial opportunities. A practical sampling strategy was employed for a sample size of 180 respondents as a descriptive study. The results showed that 32% of respondents believe that the growth rate of the stock market has been highly beneficial, and 80% of respondents are willing to invest in the stock market.